PENGARUH KEMAMPUAN KERJA (WORK ABILITY) DAN KUALITAS KERJA (WORK QUALITY) TERHADAP KUALITAS PELAYANAN PUBLIK DI DINAS SOSIAL KABUPATEN SOLOK - Pra Utari Novia Solka; Afni Yeni; Rasidah Nasrah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research was conducted at the Social Service of Solok Regency. The purpose of this study was to determine the effect of work ability and work quality on the quality of public services at the Social Service of Solok Regency. In this study, the population is people who receive services from the Social Service of Solok Regency. totaling 80 people. With this type of quantitative research and sampling technique using incidental sampling method. The data collection technique used is by using a questionnaire/questionnaire Based on multiple linear regression analysis, the variables of Work Ability and Work Quality affect the Quality of Public Services at the Social Service of Solok Regency. Y= 21.667 + 0.379X1 + 0.875X2 + e. From the t-test, it is known that the X1 variable affects the quality of public services at the Social Service of Solok Regency with a tcount of 2,323 > ttable 1,996 and sig 0.000 <0.05. X2 Variable Quality of Work has an effect on the Quality of Public Services in the Social Service of Solok Regency with tcount 6.382 > ttable 1.996 and sig 0.000 <0.05. From the Determination Test the value of R Square is 0.525. This means that the influence of the independent variable on the dependent variable is 52.5%, while the remaining 47.5% is influenced by other variables not intended in this study, such as motivational compensation, work environment, etc.